Factors associated with mortality in Covid-19 patients in a Hospital in northern Peru - Murrugarra-Suarez, Saúl (2021)
Objetive. To determine the sociodemographic and clinical risk factors related to mortality in COVID-19 patients in a Hospital in northern Peru. Material and Methods: the research was carried out in a Hospital in the north of Peru. The population was made up of 208 Clinical Histories of COVID-19 patients seen between March and July 2020. The independent variable was sociodemographic factors such as age, sex and marital status, and clinical factors such as epidemiological history, risk factors (co-morbidities) and health status and the dependent variable was Covid-19 mortality. Results: COVID-19 mortality reached 46.20% in patients older than 65 years (51.90%), male (60.40%) and married (65.40%), with an epidemiological history (37.5%) , and risk factors (comorbidity) 74.50%, mainly associated with arterial hypertension (8.2%), obesity (3.4%) and diabetes mellitus II (1.9%), and indeterminate comorbidities (Others) 6.7%. There was no mortality in patients whose health status was Stable, while patients with reserved health status and who died represented 46.2%. Conclusion: mortality from COVID-19 reached 46.20%; older than 65 years (51.90%), male (60.40%) and married (65.40%). A significant relationship was found between sociodemographic factors such as age, clinical factors (comorbidity), mostly arterial hypertension, obesity and diabetes mellitus II, and patients with a reserved health status with the mortality of COVID-19.